PENGARUH VARIASI TEKANAN INJEKTOR DAN PUTARAN TERHADAP PERFORMA DAN GAS BUANG PADA MOTOR DIESEL - Ashari, Apri; Wahab, Abd.; Junaedi, Ena Marlina (Jurnal Teknik Mesin, 2016)
The diesel fuel injection system is very important and closely related to combustion in diesel motors. The injector is a component of the diesel fuel injection system that serves to atomizes the into the combustion chamber. The combustion process in diesel motors is depend on the results of the injector fuel carburetion. The proper of injector pressure will produce better fuel carburetion and better combustion. This research aims to determine how much influence the fuel pressure in the injector of diesel engine performance and opacity smoke by setting the variation is tie up right or left to lessen the adjusting screw to add or reduce the fuel pressure. Diesel engine used were isuzu panther 2300 cc. In this experiment used engine test bed, in which the machine is placed on a stand, and then connected to dynamometer. The muffler is connected to smoke test. The parameters measured is the power, torque, specific fuel of consumption (SFC), effective specific fuel of consumption (ESFC) and opacity smoke. The results of experiment is seen the increase of power and torque after variation, and maximum at a pressure of 130 bar have 40,4 kW at 2500 rpm, and 16,8 kg.m at 1500 rpm. Pressure at 130 bar is better than pressure of 110 bar and 120 bar. The descending of opacity smoke result is seen at a pressure of 120 bar and 130 which have lowest 17,2 % and 16,8 % of opacity smoke at 1500 rpm, more advance engine turning is more high opacity smoke. More high pressure of injector and engine turning have is increase torque, effective power and reduce exhaust emission levels in diesel engine. But while the pressure increase then more high fuel consumption.